FORMULASI DAN UJI AKTIVITAS ANTIPENUAAN SPRAY GEL KOMBINASI EKSTRAK KULIT SALAK DAN LIDAH BUAYA - Saputri, Romadhiyana Kisno; Anwar, M. Rosichan; Nurhabibah, Qoiria Aini; Agustin, Lilis Nova; Rahmawati, Wahyu Desi; Afika, Zayana Dwi Nur (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
Exposure to ultraviolet light contains ROS that cause skin damage and premature aging. Spray gel with natural antioxidants can be used to prevent premature aging. This study aims to formulate and test the anti-aging activity of spray gel combination of snakefruit rind and aloe vera extracts. Spray gel was made in 6 formulas with different extract concentrations then physicochemical evaluation and in vivo anti-aging activity test were conducted. The results showed that the spray gel had a viscous liquid form, white to brownish yellow colour, oleum rosae odour, homogeneous, pH 3.3-4, viscosity 1,191-6,263 cps and average weight per spray ranging from 0.43±0.15 to 0.75±0.24. The percentage of collagen density with ImageJ Software in group F1 was 30.21%, group F2 7.34%, group F3 21.09%, group F4 7.48%, group F5 12.03% and group F6 5.25%. The combination of snakefruit extract and aloe vera extract can be formulated into an anti-aging spray gel that has good organoleptic characteristics, homogeneity, viscosity and spray pattern, but the pH value does not meet safety standards. Spray gel with natural antioxidants can be used to prevent premature aging.